A novel uncultured marine cyanophage lineage with lysogenic potential linked to a putative marine Synechococcus 'relic' prophage. Issue 4 (17th June 2019) - Flores‐Uribe, José; Philosof, Alon; Sharon, Itai; Fridman, Svetlana; Larom, Shirley; Béjà, Oded
Summary: Marine cyanobacteria are important contributors to primary production in the ocean and their viruses (cyanophages) affect the ocean microbial communities. Despite reports of lysogeny in marine cyanobacteria, a genome sequence of such temperate cyanophages remains unknown although genomic analysis indicate potential for lysogeny in certain marine cyanophages. Using assemblies from Red Sea and Tara Oceans metagenomes, we recovered genomes of a novel uncultured marine cyanophage lineage, which contain, in addition to common cyanophage genes, a phycobilisome degradation protein NblA, an integrase and a split DNA polymerase. The DNA polymerase forms a monophyletic clade with a DNA polymerase from a genomic island in Synechococcus WH8016. The island contains a relic prophage that does not resemble any previously reported cyanophage but shares several genes with the newly identified cyanophages reported here. Metagenomic recruitment indicates that the novel cyanophages are widespread, albeit at low abundance. Here, we describe a novel potentially lysogenic cyanophage family, their abundance and distribution in the marine environment.